IMPACT OF LEADERSHIP STYLES AND SERVICES ON THE QUALIY OF EARLY CHILDHOOD EDUCATION IN PUBLIC AND PRIVATE INSTITUTE - Sana Khan; Dr. Saira Taj; Asifa Younas; Saima Riaz; Ahmad Raza (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study entitled “impact of leadership style and services on the quality of early childhood education in public and private institute” The main objectives of this study are to identify the impact of leadership styles and services on quality of early childhood education.to identify the different leadership styles and services for ECE students. 200 teachers were selected from public and private institute for this study with the help of cluster sampling. This study presents a comparative analysis of leadership styles between public and private educational institutions, highlighting significant differences across several leadership styles. This research was a causal Comparative Study of leadership style and services provided by public and private institute at early childhood education level in Pakistan. Questionnaire was developed for the collection of data through surveys; among 200 teachers of public and private institutes working in district Faisalabad. Descriptive statistics was used to analyze the data while t-test and analysis of variance (ANOVA) was used to test the generated research questions. It is crystal clear that private school students had much achievement score of ECE towards ECE public school students. It is crystal clear that private school teachers had much useful teaching strategies towards public school teachers. ANOVA test results are significant. It means that the there is significant difference of leadership styles and services in both sectors. ANOVA test results are significant. It means that the there is significant difference of opinion among teacher regarding national efforts towards ECE.The results indicate that leadership styles vary markedly between public and private institutions, with private institutions excelling in instructional and constructive leadership, and in strategic leadership. These differences are not only statistically significant but also practically meaningful, emphasizing the need for context-specific leadership approaches in educational settings. Further research is recommended to validate these findings and explore the factors driving these distinctions.